Overruling uncertainty about preventative medications: the social organisation of healthcare professionals' knowledge and practices. (21st November 2019) - Cupit, Caroline; Rankin, Janet; Armstrong, Natalie; Martin, Graham P.
Abstract: In this article, we draw on an institutional ethnographic (IE) study of cardiovascular disease prevention in general practice, exploring the work of healthcare professionals who introduce a discussion of risk and preventative medications into consultations with patients. Our aim is to explicate, using IE's theoretical ontology and analytical tools, how troubling patient experiences in this clinical context are coordinated institutionally. We focus our attention on the social organisation of healthcare professionals' knowledge and front‐line practices, highlighting the textual processes through which they overrule patients' concerns and uncertainties about taking preventative medication, such that some patients feel unable to openly discuss their health needs in preventative consultations. We show how healthcare professionals activate knowledge of 'evidence‐based risk reduction' to frame patients' queries as 'barriers' to be overcome. Our analysis points not to deficiencies of healthcare professionals who lack the expertise or inclination to adequately 'share decisions' with patients, but to the ways in which their work is institutionally orientated towards performance measures which will demonstrate to local and national policymakers that they are tackling the 'burden of (cardiovascular) disease'.